Ranolazine as a therapeutic agent for diabetic cardiomyopathy: reducing endoplasmic reticulum stress and inflammation in type 2 diabetic rat model - Matin Mohyadini; Aghele Fahimi; S. Zahra Bathaie; Hamid Yaghooti (BMC Pharmacology and Toxicology)
Abstract Background Diabetic cardiomyopathy (DCM) is a significant cardiovascular complication of diabetes, characterized by structural and functional heart muscle dysfunction. Oxidative stress, endoplasmic reticulum (ER) stress, and inflammation are pivotal in the pathogenesis of DCM. Ranolazine, primarily used for angina, has demonstrated potential cardioprotective effects. This study investigates the effects of ranolazine on oxidative stress, ER stress, and inflammation in the heart tissue of type 2 diabetic rats. Methods Diabetes was induced in male Wistar rats using Nicotinamide (110 mg/kg) and Streptozotocin (60 mg/kg). The rats were then divided into control and diabetic groups, with further subdivision into ranolazine-treated and untreated subgroups. Ranolazine was administered via gavage for eight weeks. Various parameters, including body weight, heart weight, serum glucose, troponin-I levels, oxidative stress markers, ER stress markers, and inflammatory markers, were assessed. Results Diabetic rats showed increased heart weight and decreased body weight over eight weeks. Ranolazine treatment improved body weight but didn’t affect serum glucose levels. The treatment significantly lowered serum troponin-I and oxidative stress markers, increased superoxide dismutase (SOD) and glutathione (GSH) levels, and decreased malondialdehyde (MDA) concentrations. Additionally, ranolazine reduced the expression of stress-related genes (GRP78, XBP1, and NLRP3) and lowered serum IL1β levels. Conclusions The results indicate that ranolazine protects against DCM by attenuating oxidative stress, ER stress, and inflammation. Its potential as a therapeutic agent for DCM warrants further investigation.